1975
DOI: 10.3382/ps.0540688
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Body Temperature of Coturnix coturnix in Two Ambient Temperatures

Abstract: Coturnix quail were placed in an environmental chamber maintained at 21 degree C. and rectal temperatures taken. The birds were subjected to an abrupt change to 36 degree C. and the temperatures taken hourly for eight hours and at 25, 38 and 72 hours. Females had higher temperatures than males. When birds were moved to 36 degrees C. their temperatures rose rapidly and then dropped to a level higher than when birds were in the 21 degrees C. chamber. The genetic and total variation estimated from the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These results agree with Becker and Harrison (1975) and Walter and Paul (1975) who found that, Japanese quail reared for 14 days under 4 temperature treatments (20, 25, 30 and 35°C) showed negative correlation (r = -0.90) between heat production by their body and ambient temperature, with the most rapid change (-4.5% / 1°C) occurring between 20 and 25°C. The rate of change with temperature then averaged (-1.5% / 1°C) and flanked between 25 and 35°C.…”
Section: Rectal Temperaturesupporting
confidence: 92%
“…These results agree with Becker and Harrison (1975) and Walter and Paul (1975) who found that, Japanese quail reared for 14 days under 4 temperature treatments (20, 25, 30 and 35°C) showed negative correlation (r = -0.90) between heat production by their body and ambient temperature, with the most rapid change (-4.5% / 1°C) occurring between 20 and 25°C. The rate of change with temperature then averaged (-1.5% / 1°C) and flanked between 25 and 35°C.…”
Section: Rectal Temperaturesupporting
confidence: 92%
“…Gender-related differences in avian Tc are expected to occur as a function of, e.g., the reproductive state, and have been described in quails (Coturnix coturnix; [63,64]) and in great tits (P. major; [19]), while no differences were found between the Tc of males and of females of green woodhoopoes (Phoeniculus purpureus; [65]), indicating that the degree of sexual dimorphism in Tc and their controls may be a speciestypical trait. Despite sex differences in baseline Tc of great tits (higher in females than in males), their thermal responses to handling stress were of the same magnitude and were explained by gender differences in body mass, which is negatively correlated with thermal conductance [19].…”
Section: Discussionmentioning
confidence: 99%